Representações de educadores/as da Escola do Campo Água Santa – Alto Paraguai/MT : uma análise crítica do discurso - Souza, Neiva Aparecida Pires de (2021)
Education at the country in Brazil has been conquering spaces through fights from social movements, which arose in the 80s. In the 1990s, we had the first meaningful change regarding “rural education”, which is now considered as Country Education, by article 28, from Law nº 9394/96, Education Directives and Bases Law, and later recognized as Basic Education on Country. This study aims to analyse how the school educators relate their graduation, their knowledge with Orientation and Directives of Country Education. In addition, still, to reveal the representations of teachers from Água Santa school about the teaching on country school and graduation to act on Country Education. To analyze the representations of the teachers, theoretical bases of Discourse Critical analysis (ACD) were used, through Fairclogh’s (2003) representational meaning, Bhaskar’s (1998) and Barros’ (2015) Critical Realism (RC), and of transitivity system based on Halliday’s (2004) Systemic-Functional Linguistics. The research has qualitative approach and has as methodological procedures the participating observing, field notes registered in field journals, conversation rounds and formation workshop for country school educators. Data were collected by means of audio recordings. Results point out that educators do not have an early and continued formation, specific for Country Education. However, this situation could be transformed if SEDUC, through CEFAPROS, brought more public policies for formation to these educators through formation courses involving the specificities of country school.